Government of Orissa Fourth Five-Year Plan 1966-71 Report on the District and Block Plans Dhenkanal - Planning Commission (Planning Commission, 1966)
At the instances of the Planning Commission, the State Government have selected two districts, Dhenkanal and Puri for formulating comprehensive and integrated District and Block Plans for the Fourth Five-year Plan. These two districts have been selected in Orissa to serve as Pilot areas for evolving suitable methods for formulating the development plans, the prime object being to gain experience in the technique of local planning. It may be pointed out that the contribution which development plans for District and Blocks could make, in the formulation and implementation of the State Plan has been stressed long since. Although useful experience has been gained in several states, the technique available, so far, cannot be considered to be quite adequate. The difficulties encountered were as follows: In the first place, at the stage of formulating a Five-year Plan for the State, unless a fairly dependable frame-work of objectives and targets can be furnished, the proposals of local authorities go far beyond the dimensions. Secondly, schemes prepared by different Departments at the State level, when broken down and taken to the districts, are apt to become rigid and to operate without a close relationship to the special needs and problems of each area. While general patterns of development have a limited value, unless the problems and possibilities for growth are more closely identified within each district, the resources available may not be put to the best use. In the third place, Planning in the districts calls for steady and active participation on the part of experienced personnel at the State and regional levels as well as systematic investigations into local resources and problems. The knowledge and experience available in the districts need to be supplemented to a considerable extent by continuous evaluation and research. Finally, the scope of the district development plans tend to be greatly restricted if it is thought of mainly in terms of functions “decentralised” in favour of Panchayati Raj institutions. Hence, in the light of above experience gained in recent years in some of the States, it Was suggested that a district development plan should comprehend various activities envisaged in the State Five-year Plan for execution at the district level irrespective of the nature of the sponsoring authority or the location of the budget provisions.
Report on the District and Block Plans Dhenkanal
Government of Orissa